Mengenal Gaya Kepemimpinan dalam Dunia Pendidikan - Dian Eka Prihantoro (Tarbawiyah Jurnal Ilmiah Pendidikan, 2016)
This paper discusses the leadership style in the world of education. As a top leader in the school, a school principal should have performan in doing their job as a leader, particularly in the influence his subordinates. Because of this, then it is very important to use this leadership style which can be seen in the context of how he used. The leadership style that's not one color but varied according to the needs of his agency. Leadership style is the way a person in performing his task of agencies entrusted to him. In the style of good leadership, then the synergistic relationship and will occur between superiors and his subordinates for the sake of achievement of objectives and progress of his organization.